The Estimation of prostate specific antigen (PSA) concentrations in patients with prostatitis by fully automated ELISA technique. - Aldhaheri, Hussein Naeem; AlSaimary, Ihsan Edan; ALMusafer, Murtadha Mohammed (Jour Med Resh and Health Sci, 2020)
The Aim of this study was to determine Immunogenetic expression of Toll-like receptor gene clusters related to prostatitis, to give acknowledge about Role of TLR in prostatitis immunity in men from Basrah and Maysan provinces. A case–control study included 135 confirmed prostatitis patients And 50 persons as a control group. Data about age, marital status, working, infertility, family history and personal information like (Infection, Allergy, Steroid therapy, Residency, Smoking, Alcohol Drinking, Blood group, Body max index (BMI) and the clinical finding for all patients of Prostatitis were collected. This study shows the effect of PSA level in patients with prostatitis and control group, with P-value <0.0001 therefore the study shows a positive significant between elevated PSA levels and Prostatitis.